Unemployment Benefits and Unemployment Rates of Low-Skilled and Elder Workers in West Germany : A Search Equilibrium Approach - Stephan Klasen; Joachim Wolff; Andrey Launov (Institute for the Study of Labor (IZA), 2004)
In this paper we investigate whether the extension of the entitlement to unemployment benefits in the mid 80s can explain the increase in the unemployment rates of unskilled and elder workers in western Germany. To answer this question we estimate a version of the Burdett-Mortensen search equilibrium model and analyze how workers? search behaviour responded to these reforms. We try both nonparametric and fully-parametric estimation methods and identify the cases in which the nonparametric approach cannot be applied. We find that the entitlement reforms are largely responsible for the increase of unemployment among unskilled workers.
Keywords: J64; J65; 330; search equilibrium; unemployment benefit; parametric estimation; Germany; Arbeitslosigkeit; Ungelernte Arbeitskräfte; Ältere Arbeitskräfte; Arbeitsuche; Schätzung; Deutschland